Glue coating liquid and new energy battery spacing adhesive tape
By adding thermal filler to the glue coating liquid of the battery space tape and designing a hollow structure, the existing battery space tape is solved by hindering ventilation and occupying space, and better heat dissipation and energy storage density are achieved.
Patent Information
- Application Number
- CN202411738352.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-25
AI Technical Summary
The entire backing structure of the existing battery space tape hinders ventilation of the internal components of the battery, reduces heat dissipation effect, and occupies the internal space of the battery, resulting in a reduction in energy storage density.
Add thermal filler to the glue coating liquid to improve its thermal conductivity, and design the hollow gap in the battery space tape to reduce the use of adhesive layer and thus improve the utilization of the internal space of the battery.
By improving the thermal conductivity of the glue coating liquid and optimizing the tape structure, the heat dissipation effect of the battery is enhanced, the battery is overheated, and the energy storage density is improved.
Smart Images

Figure CN119684936A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive tapes, and in particular to a glue coating liquid and a new energy battery spacer tape. Background Art
[0002] Battery spacer tape is used in the manufacturing and assembly process of lithium batteries to fix and insulate the battery components. Existing battery spacer tapes are usually coated with glue on one side of the tape substrate to form a back glue area. Since the existing glue coating liquid does not have a heat dissipation effect, and the structure of the entire back glue will hinder the ventilation of the internal components of the battery and reduce the heat dissipation effect of the battery; in addition, the tape with a full-surface back glue structure will occupy more space inside the battery, reducing the energy storage density of the battery; therefore, further improvement is urgently needed. Summary of the invention
[0003] In order to overcome at least one of the technical problems existing in the prior art, the present invention provides a glue coating liquid and a new energy battery spacer tape.
[0004] The technical solution of the present invention is as follows:
[0005] A glue coating liquid comprises the following components in parts by weight: 80 to 120 parts of acrylate glue; 10 to 20 parts of thermal conductive filler; 40 to 80 parts of solvent; 0.1 to 1 part of leveling agent; and 0.1 to 1 part of curing agent.
[0006] The invention adds a heat-conducting filler into the glue coating liquid so that the glue coating liquid has heat-conducting performance.
[0007] Preferably, the glue coating liquid comprises the following components in parts by weight: 100 parts of acrylate glue; 15 parts of thermal conductive filler; 50 parts of solvent; 0.5 parts of leveling agent; and 0.5 parts of curing agent.
[0008] Preferably, the glue coating liquid further comprises a color paste, and the weight portion of the color paste is 3 to 6 parts.
[0009] Most preferably, the color paste has 5 parts by weight.
[0010] Preferably, the color of the color paste is green, dark green or blue.
[0011] Preferably, the solvent is ethyl acetate.
[0012] Preferably, the acrylic adhesive is an acrylic pressure-sensitive adhesive.
[0013] Preferably, the thermally conductive filler comprises boron nitride and magnesium oxide.
[0014] Further preferably, the weight ratio of boron nitride to magnesium oxide in the thermally conductive filler is 3 to 5:1.
[0015] Most preferably, the weight ratio of boron nitride to magnesium oxide in the thermally conductive filler is 4:1.
[0016] Preferably, the thermally conductive filler is a modified thermally conductive filler;
[0017] The modified thermally conductive filler is prepared by the following method:
[0018] Take an ethanol aqueous solution, then add a modifier, and stir evenly to obtain a modifier ethanol solution;
[0019] Preheat the thermal conductive filler at 60-90°C for 30-40 minutes, then stir at 100-150°C, and spray the modifier ethanol solution into the thermal conductive filler in the form of mist; continue stirring at 100-150°C for 2-4 hours after spraying; after stirring, the modified thermal conductive filler is obtained.
[0020] The inventors found in further research that adding a modified thermal conductive filler obtained by modifying boron nitride and magnesium oxide by the above method into the glue coating liquid can significantly improve the thermal conductivity of the glue coating liquid compared to adding an unmodified thermal conductive filler composed of boron nitride and magnesium oxide.
[0021] The inventors found in further research that adding modified thermal conductive fillers obtained by modifying boron nitride and magnesium oxide by the above method to the glue coating liquid can greatly improve the peel strength of the glue coating liquid after bonding, compared with adding unmodified thermal conductive fillers composed of boron nitride and magnesium oxide.
[0022] Preferably, the volume fraction of ethanol in the ethanol aqueous solution is 60-80%.
[0023] Most preferably, the volume fraction of ethanol in the ethanol aqueous solution is 70%.
[0024] Preferably, the weight ratio of the ethanol aqueous solution to the modifier is 100:3-6.
[0025] Most preferably, the weight ratio of the ethanol aqueous solution to the modifier is 100:5.
[0026] Preferably, the usage ratio of the thermal conductive filler to the modifier is 100:2-5.
[0027] Most preferably, the ratio of the thermal conductive filler to the modifier is 100:3.
[0028] Preferably, the weight ratio of boron nitride to magnesium oxide in the thermally conductive filler is 3 to 5:1.
[0029] Most preferably, the weight ratio of boron nitride to magnesium oxide in the thermally conductive filler is 4:1.
[0030] Preferably, the modifier comprises 3-mercaptopropyltrimethoxysilane, pentasodium ethylenediaminetetramethylenephosphonate and trimethylammonium soya oil chloride.
[0031] Preferably, the weight ratio of 3-mercaptopropyltrimethoxysilane, pentasodium ethylenediaminetetramethylenephosphonate and trimethylammonium soyaoil chloride in the modifier is 1-3:1-3:3-6.
[0032] Most preferably, the weight ratio of 3-mercaptopropyltrimethoxysilane, pentasodium ethylenediaminetetramethylenephosphonate and trimethylammonium soyaoil chloride in the modifier is 2:2:5.
[0033] The inventors found in further research that the composition of the modifier of the present invention is very critical; the modified thermal conductive filler modified by the modifier composed of 3-mercaptopropyl trimethoxysilane, pentasodium ethylenediaminetetramethylenephosphonic acid and trimethylammonium soy oil chloride must be used at the same time to significantly improve the peel strength of the glue coating liquid after bonding. However, the modified thermal conductive filler modified by the modifier composed of only any two of the three compositions of 3-mercaptopropyl trimethoxysilane, pentasodium ethylenediaminetetramethylenephosphonic acid and trimethylammonium soy oil chloride cannot significantly improve the peel strength of the glue coating liquid after bonding.
[0034] The present invention also provides a new energy battery spacer tape, in which the pressure-sensitive adhesive layer is formed by coating the above-mentioned glue coating liquid.
[0035] The pressure-sensitive adhesive layer is formed by coating the glue coating liquid with heat dissipation function of the present invention, which helps to improve the heat dissipation effect of the new energy battery spacer tape.
[0036] Preferably, the new energy battery spacer tape comprises a substrate, one side of the substrate is a non-silicone release agent layer, and the other side of the substrate is a pressure-sensitive adhesive layer.
[0037] Preferably, the thickness of the pressure-sensitive adhesive layer is 0.01-0.1 mm.
[0038] Most preferably, the thickness of the pressure-sensitive adhesive layer is 0.5 mm.
[0039] Preferably, the pressure-sensitive adhesive layer is a colored pressure-sensitive adhesive layer.
[0040] Further preferably, the colors include green, dark green and blue.
[0041] Most preferably, the color is blue.
[0042] Preferably, the non-silicone release agent layer is formed by coating a release agent coating liquid.
[0043] Further preferably, the release agent coating liquid comprises the following raw material components in parts by weight: 80 to 120 parts of solvent; and 0.1 to 1 part of non-silicone release agent.
[0044] Most preferably, the release agent coating liquid comprises the following raw material components in parts by weight: 100 parts of solvent; 0.5 parts of non-silicone release agent.
[0045] Preferably, the solvent is toluene.
[0046] Preferably, the non-silicone release agent includes but is not limited to PEELOIL1010 non-silicone release agent, Ichemco non-silicone release agent K100H, K100D, K100ES, RL-600 non-silicone release agent, one or a mixture of two thereof.
[0047] Preferably, the pressure-sensitive adhesive layer comprises an adhesive-backed area and a non-adhesive-backed area; the non-adhesive-backed area is located in the middle of the adhesive-backed area to form a hollow area; and the adhesive-backed area is formed by coating the above-mentioned glue coating liquid.
[0048] Beneficial effects: The present invention first provides a glue coating liquid with a new composition; by adding thermally conductive fillers into the glue coating liquid, the glue coating liquid has thermal conductivity; in addition, the present invention also provides a new structure of a new energy battery spacer tape, the new energy battery spacer tape is designed with a hollow gap portion, and this gap portion has no adhesive layer, forming a certain spacing space inside the battery, which can improve the utilization rate of the internal space of the battery and increase the energy storage density of the battery while playing the role of insulation and fixation; in addition, combined with the pressure-sensitive adhesive layer formed by coating the glue coating liquid with heat dissipation effect described in the present invention, the new energy battery spacer tape can have a better heat dissipation effect and prevent the battery from overheating. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a physical picture of the new energy battery spacer tape of the present invention. DETAILED DESCRIPTION
[0050] The present invention is further explained below in conjunction with specific examples, but the examples do not limit the present invention in any form.
[0051] The acrylic adhesive used in the following examples is AROSET from Ashland, USA. TM 951063 acrylic pressure-sensitive adhesive; the remaining raw materials are conventional raw materials that can be purchased by those skilled in the art.
[0052] Example 1 Preparation of glue coating liquid
[0053] Raw materials by weight: 100 parts of acrylate glue; 15 parts of thermal conductive filler; 50 parts of ethyl acetate; 0.5 parts of leveling agent; 0.5 parts of curing agent;
[0054] The thermal conductive filler is composed of boron nitride and magnesium oxide in a weight ratio of 4:1.
[0055] Preparation method of glue coating liquid: uniformly mix the above raw materials in parts by weight to obtain the glue coating liquid.
[0056] Example 2 Preparation of glue coating liquid
[0057] Raw materials by weight: 100 parts of acrylate glue; 15 parts of modified thermal conductive filler; 50 parts of ethyl acetate; 0.5 parts of leveling agent; 0.5 parts of curing agent;
[0058] The modified thermally conductive filler is prepared by the following method:
[0059] (1) taking an ethanol aqueous solution, then adding a modifier, and stirring to obtain an ethanol solution of the modifier; wherein the volume fraction of ethanol in the ethanol aqueous solution is 70%; the weight ratio of the ethanol aqueous solution to the modifier is 100:5; the modifier is composed of 3-mercaptopropyltrimethoxysilane, pentasodium ethylenediaminetetramethylenephosphonate, and trimethylammonium soya oil chloride in a weight ratio of 2:2:5;
[0060] (2) preheating the thermal conductive filler at 70° C. for 30 min, stirring at 120° C., and spraying the modifier ethanol solution into the thermal conductive filler in the form of mist; stirring at 120° C. for 3 h after spraying; obtaining the modified thermal conductive filler after stirring; the thermal conductive filler is composed of boron nitride and magnesium oxide in a weight ratio of 4:1; and the ratio of the thermal conductive filler to the modifier is 100:3;
[0061] Preparation method of glue coating liquid: uniformly mix the above raw materials in parts by weight to obtain the glue coating liquid.
[0062] Example 2 Preparation of glue coating liquid
[0063] Raw materials by weight: 100 parts of acrylate glue; 15 parts of modified thermal conductive filler; 5 parts of blue color paste; 50 parts of ethyl acetate; 0.5 parts of leveling agent; 0.5 parts of curing agent;
[0064] The modified thermally conductive filler is prepared by the following method:
[0065] (1) taking an ethanol aqueous solution, then adding a modifier, and stirring to obtain an ethanol solution of the modifier; wherein the volume fraction of ethanol in the ethanol aqueous solution is 70%; the weight ratio of the ethanol aqueous solution to the modifier is 100:5; the modifier is composed of 3-mercaptopropyltrimethoxysilane, pentasodium ethylenediaminetetramethylenephosphonate, and trimethylammonium soya oil chloride in a weight ratio of 2:2:5;
[0066] (2) preheating the thermal conductive filler at 70° C. for 30 min, stirring at 120° C., and spraying the modifier ethanol solution into the thermal conductive filler in the form of mist; stirring at 120° C. for 3 h after spraying; obtaining the modified thermal conductive filler after stirring; the thermal conductive filler is composed of boron nitride and magnesium oxide in a weight ratio of 4:1; and the ratio of the thermal conductive filler to the modifier is 100:3;
[0067] Preparation method of glue coating liquid: uniformly mix the above raw materials in parts by weight to obtain the glue coating liquid.
[0068] Comparative Example 1 Preparation of Glue Coating Liquid
[0069] The difference between Comparative Example 1 and Example 2 is that the composition of the modifier is different during the preparation of the modified thermal conductive filler; the modifier in Comparative Example 1 is composed of 3-mercaptopropyltrimethoxysilane and trimethylammonium soya oil chloride in a weight ratio of 2:5. The rest is the same as Example 2.
[0070] Comparative Example 2 Preparation of Glue Coating Liquid
[0071] The difference between Comparative Example 2 and Example 2 is that the composition of the modifier is different during the preparation of the modified thermal conductive filler; the modifier in Comparative Example 2 is composed of pentasodium ethylenediaminetetramethylenephosphonate and trimethylammonium soya oil chloride in a weight ratio of 2:5. The rest is the same as Example 2.
[0072] Comparative Example 3 Preparation of Glue Coating Liquid
[0073] The difference between Comparative Example 3 and Example 2 is that the composition of the modifier is different during the preparation of the modified thermal conductive filler; the modifier in Comparative Example 3 is composed of 3-mercaptopropyltrimethoxysilane and pentasodium ethylenediaminetetramethylenephosphonate in a weight ratio of 1:1. The rest is the same as Example 2.
[0074] The 180° peeling force of the glue coating solutions prepared in Examples 1 to 3 and Comparative Examples 1 to 3 after bonding was tested with reference to GB / T 2792-1998 standard; the thermal conductivity of the glue coating solutions prepared in Examples 1 to 3 and Comparative Examples 1 to 3 after bonding was tested with reference to GB / T42919.1-2023 standard; the test results are shown in Table 1.
[0075] Table 1. Glue coating liquid performance test results
[0076]
[0077]
[0078] It can be seen from the experimental results in Table 1 that the thermal conductivity of the glue coating liquid prepared in Example 1 is 1.8 W / (m·K); this shows that the present invention adds thermal conductive fillers to the glue coating liquid, so that the glue coating liquid has thermal conductivity.
[0079] It can be seen from the experimental results in Table 1 that the thermal conductivity of the glue coating liquid prepared in Example 2 is further significantly higher than that in Example 1; this shows that adding the modified thermal conductive filler obtained by modifying boron nitride and magnesium oxide by the above method to the glue coating liquid can significantly improve the thermal conductivity of the glue coating liquid compared to adding the unmodified thermal conductive filler composed of boron nitride and magnesium oxide.
[0080] It can be seen from the experimental results in Table 1 that the 180° peeling force of the glue coating liquid prepared in Example 2 is further significantly higher than that of Example 1; this shows that adding the modified thermal conductive filler obtained by modifying boron nitride and magnesium oxide by the above method to the glue coating liquid can greatly improve the peeling strength of the glue coating liquid after bonding, compared with adding the unmodified thermal conductive filler composed of boron nitride and magnesium oxide.
[0081] From the experimental results in Table 1, it can be seen that the 180° peeling strength of the glue coating liquid prepared in Comparative Examples 1 to 3 is much less improved than that of Example 2 compared with Example 1; this shows that the composition of the modifier of the present invention is very critical; the modified thermal conductive filler modified by the modifier composed of 3-mercaptopropyl trimethoxysilane, pentasodium ethylenediaminetetramethylenephosphonic acid and trimethylammonium soy oil chloride must be used at the same time to significantly improve the peeling strength of the glue coating liquid after bonding. However, the modified thermal conductive filler modified by only any two of the three modifiers composed of 3-mercaptopropyl trimethoxysilane, pentasodium ethylenediaminetetramethylenephosphonic acid and trimethylammonium soy oil chloride cannot significantly improve the peeling strength of the glue coating liquid after bonding.
[0082] Example 4 Preparation of new energy battery spacer tape
[0083] The new energy battery spacer tape includes a substrate, one side of the substrate is a non-silicone release agent layer, and the other side is a pressure-sensitive adhesive layer; the pressure-sensitive adhesive layer includes a back-adhesive area and a non-back-adhesive area; the non-back-adhesive area is located in the middle of the back-adhesive area to form a hollow area; the back-adhesive area is formed by coating the glue coating liquid prepared by any method of Examples 1 to 3.
[0084] The thickness of the pressure-sensitive adhesive layer is 0.5 mm;
[0085] The release agent coating liquid comprises the following raw material components in parts by weight: 100 parts of toluene; 0.5 parts of non-silicon release agent; the non-silicon release agent includes but is not limited to one or a mixture of two of PEELOIL1010 non-silicon release agent, Ichemco non-silicon release agent K100H, K100D, K100ES, and RL-600 non-silicon release agent.
[0086] Preparation method: set the coating head mold to the back glue width and gap width, apply the release agent coating liquid on one side of the substrate and the glue coating liquid on the other side, and after the coating is completed, heat and dry it in an oven and then collect it into a roll to obtain the new energy battery spacer tape.
Claims
1. A glue coating liquid, characterized in that: The invention comprises the following components in parts by weight: 80 to 120 parts of acrylate glue; 10 to 20 parts of thermal conductive filler; 40 to 80 parts of solvent; 0.1 to 1 part of leveling agent; and 0.1 to 1 part of curing agent.
2. The glue coating liquid according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 100 parts of acrylate glue; 15 parts of thermal conductive filler; 50 parts of solvent; 0.5 parts of leveling agent; and 0.5 parts of curing agent.
3. The glue coating liquid according to claim 1, characterized in that: The glue coating liquid also contains color paste, and the weight portion of the color paste is 3 to 6 parts.
4. The glue coating liquid according to claim 1, characterized in that: The acrylic adhesive is an acrylic pressure-sensitive adhesive.
5. The glue coating liquid according to claim 1, characterized in that: The thermal conductive filler comprises boron nitride and magnesium oxide.
6. A new energy battery spacer tape, characterized in that: The pressure-sensitive adhesive layer in the new energy battery spacer tape is formed by coating the glue coating liquid described in any one of claims 1 to 5.
7. The new energy battery spacer tape according to claim 6, characterized in that: The new energy battery spacer tape comprises a substrate, one side of the substrate is a non-silicone release agent layer, and the other side of the substrate is a pressure-sensitive adhesive layer.
8. The new energy battery spacer tape according to claim 7, characterized in that: The thickness of the pressure-sensitive adhesive layer is 0.01-0.1 mm.
9. The new energy battery spacer tape according to claim 7, characterized in that: The non-silicon release agent layer is formed by coating a release agent coating liquid; the release agent coating liquid comprises the following raw material components in parts by weight: 80 to 120 parts of a solvent; and 0.1 to 1 part of a non-silicon release agent.
10. The new energy battery spacer tape according to claim 9, characterized in that: The pressure-sensitive adhesive layer comprises an adhesive backing area and a non-adhesive backing area; the non-adhesive backing area is located in the middle of the adhesive backing area to form a hollow area; the adhesive backing area is coated with the glue coating liquid described in any one of claims 1 to 5.